L1 Cognitive Skills Transfer in the Process of Learning L2 of Dependent Scripts - Dewi, Utami; Sibarani, Berlin; Sumarsih, Sumarsih (Association of Language Teachers in Southeast Asia (ALTSA), 2020)
Language transfer is one of the important areas in second language acquisition research. This study aims to describe the process of transfer L1, Bahasa Indonesia, cognitive skills to L2, English, cognitive skills of dependent scripts. Cognitive skills are the skills that support decoding, such as rapid automatized naming (RAN) and working memory (WM). This research was conducted with descriptive qualitative research design, with case study.Ã‚Â The subjects of the study were 15 students who speak Bahasa as the first language (L1) and learn English as the second language (L2). Bahasa and English are the language which have the same scripts, dependent scripts. The subjects were given the rapid automatized naming (RAN) test and working memory (WM) test. The data of this study was analyzed with two data analysis techniques, they were non-parametric statistics and qualitative data analysis. The finding of this study was that there was no significantly transfer of cognitive skills from L1, Bahasa, to L2, English. It can be seen from the process of transfer RAN and WM as the subskills, that most of the students made different errors both in L1 and L2 RAN and WM, and they have different levels of achievement in L1 and L2 cognitive skills.